2007
DOI: 10.1007/978-3-540-77156-2_41
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Covert Conflict

Abstract: Often an attacker tries to disconnect a network by destroying nodes or edges, while the defender counters using various resilience mechanisms. Examples include a music industry body attempting to close down a peer-to-peer file-sharing network; medics attempting to halt the spread of an infectious disease by selective vaccination; and a police agency trying to decapitate a terrorist organisation. Albert, Jeong and Barabási famously analysed the static case, and showed that vertex -order attacks are effective ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Nagaraja and Anderson extend this to the dynamic case. In their model, the attacker can remove a certain number of nodes at each round, after which the defenders recruit other nodes to replace them [97]. They studied how attack and defence interact using multi-round simulations, and found that forming localised clique structures at key network points works reasonably well while defences based on rings did not work well at all.…”
Section: Network Topology and Information Securitymentioning
confidence: 99%
“…Nagaraja and Anderson extend this to the dynamic case. In their model, the attacker can remove a certain number of nodes at each round, after which the defenders recruit other nodes to replace them [97]. They studied how attack and defence interact using multi-round simulations, and found that forming localised clique structures at key network points works reasonably well while defences based on rings did not work well at all.…”
Section: Network Topology and Information Securitymentioning
confidence: 99%
“…We are not aware of literature using scale-free topologies to model interdependent security or correlated risk in cyber-insurance, although this family of graphs is wellestablished in the areas of reliability modeling and distributed defense for its good fit with real-world networks [AJB00,NA06].…”
Section: Network Topology Gmentioning
confidence: 99%
“…al. [25] used game theory and network analysis to suggest effective attacks and defenses against networks and network connectivity. BotGrep [26] identifies botnet communities using random walks to detect dense community structures.…”
Section: Related Workmentioning
confidence: 99%